The relationship between big five personality traits and job performance among employees at Miri City Council, Sarawak / Saloma Emang - Emang, Saloma (2010)
The issues of personality have greatly becoming essential to all organizations in today’s working environment especially since personality tends to determine the capability of employees to perform in the organization. Therefore, this study is carried out as an attempt to highlight the role of personality towards the job performance by the employees at the Miri City Council, Sarawak. In order to identify the relationship between personality and job performance, 180 sets of questionnaire has been distributed to the Miri City Council, Sarawak. Five dimensions of big five personality traits had been used to represent personality whereby each of the five dimension of this model including extroversion, agreeableness, conscientiousness, openness to experience and neuroticism has been tested with the job performance. Based on the objective and research questions developed, the findings show that the employees in the organizations had high level of extroversion, agreeableness, conscientiousness and openness to experience as well as a moderate level of neuroticism. Furthermore, based on the findings of correlation, it was found extroversion, agreeableness, conscientiousness and openness to experience has a positive relationship with job performance, while neuroticism were found to have a negative relationship to the job performance. Therefore, employees with high level of extroversion, agreeableness, conscientiousness and openness to experience tend to perform high level of job performance.